2013
DOI: 10.1021/jf4019195
|View full text |Cite
|
Sign up to set email alerts
|

Elevating Bioavailability of Curcumin via Encapsulation with a Novel Formulation of Artificial Oil Bodies

Abstract: Utilization of curcumin has been limited due to its poor oral bioavailability. Oral bioavailability of hydrophobic compounds might be elevated via encapsulation in artificial seed oil bodies. This study aimed to improve oral bioavailability of curcumin via this encapsulation. Unfortunately, curcumin was indissoluble in various seed oils. A mixed dissolvent formula was used to dissolve curcumin, and the admixture was successfully encapsulated in artificial oil bodies stabilized by recombinant sesame caleosin. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 27 publications
1
30
0
1
Order By: Relevance
“…resulted in 1% bioavailability of curcumin in rat plasma [96]. It has been also observed that oral administration of curcumin (1,000 mg/kg) in rats showed 15 ng/mL in blood plasma at 50 minutes [97]. In contrast to rodents, oral dosing of 4-8 g of curcumin in humans showed peak plasma levels of 0.41-1.75 µM after 1 hour of dosing [98].…”
Section: Bioavailability Of Curcuminmentioning
confidence: 99%
“…resulted in 1% bioavailability of curcumin in rat plasma [96]. It has been also observed that oral administration of curcumin (1,000 mg/kg) in rats showed 15 ng/mL in blood plasma at 50 minutes [97]. In contrast to rodents, oral dosing of 4-8 g of curcumin in humans showed peak plasma levels of 0.41-1.75 µM after 1 hour of dosing [98].…”
Section: Bioavailability Of Curcuminmentioning
confidence: 99%
“…Likewise, Yang et al (2007) determined that curcumin administration (500 mg/kg) showed the 1% bioavailability of curcumin in the plasma of freely moving rats. Similarly, 15 µg/ml curcumin was reported at the blood plasma level at 50 min after oral curcumin administration (1000 mg/ kg) in rats (Chang et al 2013). Moreover, the orally administered curcumin (4-8 g) in humans exhibited the peak plasma levels of 0.41-1.75 µM (Cheng et al 2001).…”
Section: Pharmacokinetics Of Curcuminmentioning
confidence: 85%
“…A previous study has found that a maximum serum level of 1.35 ± 0.23 μg/mL is observed at 0.83 h after oral administration of curcumin (2 g/kg) in rats [122]. Other studies show that oral intake of curcumin results in 1% bioavailability in rat plasma [123,124]. In contrast to rodents, 2 g/kg, the same dosing in the study in rats above, of curcumin administered orally to humans leads to extremely low concentrations (0.006 ± 0.005 μg/mL at 1 h) in serum [122].…”
Section: Bioavailability Safety Tolerability and Pharmacokineticsmentioning
confidence: 95%